(untitled) (Journal of Institute of Medicine Nepal, 2011)
Submandibular thyroid is one of the rare locations of ectopic thyroid tissue. Only few cases have been reported in the literature. We report a case of 16 year old female patient presenting with ectopic submandibular thyroid tissue. Diagnosis was based on ultrasound and cytology. Keywords: Nepal; submandibular ectopic thyroid DOI: http://dx.doi.org/10.3126/joim.v32i2.4948 Journal of Institute of Medicine, August, 2010; 32: 53-55